Training in Managerial Leadership Among Owners of Small to Medium Businesses in Makassar to Increase Leadership Effectiveness [Pelatihan Kepemimpinan Manajerial pada Pemilik Usaha Kecil Menengah (UKM) di Kota Makassar untuk Meningkatkan Efektivitas Kepemi - Andi Muhammad Aditya; Arief Fahmie; Emi Zulaifah (ANIMA Indonesian Psychological Journal, 2020)
There are several problems which threaten Small to Medium Businesses (Usaha Kecil Menengah - UKM) in the City of Makassar, South Sulawesi, Indonesia: the low quality of the managerial abilities of owners of UKM, the rapid growth of modern retail shops, and the rise in the amount of better quality technological products entering the city. The goal of this research was to construct a model of the development of managerial effectiveness, using a competency concept, based upon 12 levels of behaviour and 10 types of managerial roles. The research method used was action research, in the form of the implementation of managerial leadership training. This research also developed an indicator of managerial leadership behaviors, by compiling a matrix based upon managerial roles and leadership behaviours. Eight owners of UKM in Makassar were participants in the research. The results of the study, in general, indicated an increase in the levels of managerial leadership of the participants who received the training. The impact of an increase in competence and effectiveness of managerial leadership could cause UKM owners enjoy an increase in competitiveness, in the managing of their enterprises. Terdapat beberapa permasalahan yang menjadi ancaman dihadapi Usaha Kecil Menengah (UKM) di kota Makassar yaitu rendahnya kualitas kemampuan pemilik UKM, pertumbuhan toko ritel modern yang pesat, dan meningkatnya produk yang masuk ke Kota Makassar dengan kualitas teknologi yang lebih baik. Tujuan penelitian ini adalah membuat sebuah model pengembangan efektivitas kepemimpinan dengan menggunakan konsep kompetensi berdasarkan 12 tingkat perilaku kepemimpinan dan 10 jenis peran manajerial. Metode penelitian ini adalah action research berupa implementasi pelatihan kepemimpinan manajerial. Penelitian ini juga mengembangkan sebuah indikator perilaku kepemimpinan manajerial dengan menyusun matriks berdasarkan peran manajerial dan perilaku kepemimpinan. Delapan orang pemilik UKM di Kota Makassar menjadi partisipan penelitian. Hasil studi secara umum menunjukkan adanya peningkatan level kepemimpinan manajerial pada partisipan yang menerima pelatihan. Dampak peningkatan kompetensi efektivitas kepemimpinan manajerial dapat membuat para pemilik UKM memiliki peningkatan daya saing dalam mengelola usahanya.